Albert Einstein and Bernard Lonergan on Empirical Method - Teevan, Donna (Zygon, 2002)
In the science–and–theology dialogue, it becomes imperative that theologians develop sophistication in empirical method. Albert Einstein stated that to understand what physicists do we should not listen to what they say but watch what they do. Still, he wrote incisively about method in physics. Theologian and philosopher Bernard Lonergan developed a methodical approach to theology that was influenced by the natural sciences. I present Einstein's thought on epistemology and the relationship between sense experience and theory. I then turn to Lonergan's understanding of empirical method in the natural sciences, generalized empirical method, and his treatment of Einstein's work.